Quebec City's Ship Carpenters, 1840 to 1893: Working Class Self-Organization on the Waterfront - Mathieu, Jean-Philip (University of Ottawa (Canada), 2010)
In the mid-nineteenth century, the construction of wooden sailing vessels became the single most important employer in Quebec City. Thousands of people worked as shipwrights in the shipbuilding industry, but ship carpenters were the backbone of the trade. These workers displayed an extraordinary capacity for mobilization, being responsible for some of Canada's earliest labour organizations, starting in 1840 with the Societe amicale et bienveillante des charpentiers de vaisseaux de Quebec. This study demonstrates that ship carpenters' impressive capacity for organization was the result of the trade's remarkable ethnic homogeneity, as no less than 90% of ship carpenters were French Canadian, and most lived together in the working class suburb of Saint Roch. This homogeneity allowed ship carpenters to avoid the bitter internecine conflict that plagued the early labour movement, and allowed them to become part of the vanguard of the Canadian working class.
Keywords: History, Canadian.